1992
DOI: 10.7326/0003-4819-117-9-751
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Housestaff Diagnostic Skills Using a Cardiology Patient Simulator

Abstract: Housestaff had difficulty establishing a correct diagnosis for simulations of three common valvular heart diseases. Accurate recognition of a few "key" observations was associated with a correct diagnosis in two of the three diseases. Teaching housestaff to elicit and interpret a few critical signs accurately may improve their physical diagnosis abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(66 citation statements)
references
References 6 publications
4
62
0
Order By: Relevance
“…Cardiac auscultation skills in various training programs, including pediatrics, have been documented to be poor. [6][7][8] Four conditions (patent ductus arteriosus, ventricular septal defect, innocent murmur, and pulmonary branch murmur of infancy) accounted for 91% of diagnoses for patients with murmurs. Initially developing stethoscope skills among pediatric residents for the detection of these conditions should fulfill clinical needs frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac auscultation skills in various training programs, including pediatrics, have been documented to be poor. [6][7][8] Four conditions (patent ductus arteriosus, ventricular septal defect, innocent murmur, and pulmonary branch murmur of infancy) accounted for 91% of diagnoses for patients with murmurs. Initially developing stethoscope skills among pediatric residents for the detection of these conditions should fulfill clinical needs frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies evaluating skills in performing physical examinations by medical students, housestaff , and even medical school faculty have uniformly shown a 20% to 80% error rate in recognizing actual or simulated fi ndings (1)(2)(3)(4)(5). Such defi ciencies An underappreciated problem with auscultation Allen B. Weisse, MD can only be exacerbated by improper auscultatory technique such as that described here.…”
mentioning
confidence: 96%
“…The decline in cardiovascular (CV) physical examination (PE) skills, especially for cardiac auscultation, has been well documented (2) . Studies assessing PE skills have shown important mistake and oversight rates for physicians at all levels of training (3) . Bedside echocardiography can bring important anatomical and hemodynamic information for the management of hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%